Adiabatic triplet state tautomerization of p-hydroxyacetophenone in aqueous solution - Klíčová, Ĺubica; Šebej, Peter; Šolomek, Tomáš; Hellrung, Bruno; Slavíček, Petr; Klán, Petr; Heger, Dominik; Wirz, Jakob (The journal of physical chemistry. A, 2012)
The primary photophysical processes of p-hydroxyacetophenone (HA) and the ensuing proton transfer reactions in aqueous solution were investigated by picosecond pump-probe spectroscopy and nanosecond laser flash photolysis. Previous studies have led to mutually inconsistent conclusions. The combined data allow us to rationalize the excited-state proton transfer processes of HA in terms of a comprehensive, well-established reaction scheme. Following fast and quantitative ISC to the triplet state, (3)HA*, adiabatic proton transfer through solvent water simultaneously forms both the anion, (3)A(-)*, and the quinoid triplet enol tautomer, (3)Q*. The latter subsequently equilibrates with its anion (3)A(-)*. Ionization and tautomerization are likely to compete with the desired release reactions of p-hydroxyphenacyl photoremovable protecting groups.